IMPLEMENTASI KEBIJAKAN PEMERATAAN MUTU PENDIDIKAN DI KECAMATAN PAMONA BARAT KABUPATEN POSO - MBAE, AGHNES TRESYA; OGOTAN, MARTHA; PALAR, NOVIE ANDERS (JURNAL ADMINISTRASI PUBLIK, 2018)
Based on Law No. 20 of 2003 concerning the National Education System, article 5 paragraph (1) statesthat "Every citizen has the same right to obtain quality education", and article 11, paragraph (1) states"Government and Regional Government must provide services and facilities and guarantee theimplementation of quality education for every citizen without discrimination. Basically Education aims toeducate the life of the nation and improve human resources that are good and smart. In addition,education is expected to be able to improve the quality of life and can produce educated people who havefaith, noble character, knowledge, skill, personality and responsibility. as mandated by the 1945Constitution which requires the government to be responsible in educating the life of the nation andcreating general welfare. This study uses a qualitative method adapted to the title and problem, thepurpose of this study is to find out how policy implementation in this case the quality distribution ofeducation in West Pamona District, Poso Regency, Central Sulawesi Province.Keywords: Policy Implementation, Quality and Education Equity.